Applicability of international prognostic index in NON HODGKIN’S LYMPHOMA IN PAKISTAN - Aziz, Zeba; Sana, Sherjeel; Saeed, Sarah; Akram, Mohammad (Journal of Ayub Medical College Abbottabad, 2004)
Background: Aggressive non Hodgkin’s Lymphomas (NHL) are common in Southeast Asia, Middle East and Africa. Data on survival with relation to prognostic factors is scarce. The primary objective of the study was to evaluate the applicability of International Prognostic Index (IPI) to predict overall survival (OS) and disease free survival (DFS) in developing countries. Methods: Two hundred and nineteen patients of NHL consecutively presenting to the Department of Oncology, Jinnah Hospital Lahore between August 1998 to July 2000 were analyzed. All patients underwent initial staging according to Ann Arbor staging system. The patients were categorized by five independent risk factors: patient age, disease stage, serum lactate dehydrogenase (LDH) levels, performance status, and number of extranodal sites involved. Patients were divided into three risk categories Low (0 or one risk factors), Intermediate (2 risk factors) and High (3 or more risk factors). Results: According to IPI low risk category comprised of 15%, intermediate 21% and high 64% of patients, Overall survival (OS) for 2 years and 5 years (n=197) was (69%), (51%), (32%) and (64%), (46%), (13%) respectively (p=0.0008). Disease free survival (DFS) for 2 years and five years (n=197) was (66%), (43%), (34%) and (66%), (43%), (18%) respectively. Age adjusted (‰¤ 60) DFS for 2 and 5 years (n=164) was (70%), (45%), (40%) and (63%), (45%) (19%)respectively. OS for 2 and 5 years (n=164) was (71%), (52%), (34%) and (64%), (46%),(11%) respectively (p=0.0013). Conclusions: The IPI accurately predicted survival in our population. Modification of treatment protocols according to specific risk groups will be beneficial to the developing countries with limited resources. Key Words: Developing Countries, International Prognostic Index, Survival, Non Hodgkin’s Lymphoma